Genetic variability among soybean biparental crosses evaluated by multivariate analysis (Bioscience Journal, 2015)
This work aims to study the genetic variability of 22 biparental crosses of soybean through multivariate techniques. The experiment was carried out in a randomized complete block design with three replications, consisting of 110 genotypes from 22 biparental crosses and cultivars UFUS Riqueza, UFUS Impacta, UFUS Xavante UFUS Millionária and MSoy 8211 which were used as control. The characters evaluated were number of days until flowering and until maturity, plant height at flowering and at maturity, number of pods with one, two or three seeds, total number of pods, weight of plant and first pod yield. The population evaluated showed genetic variability for most traits. Plant height at maturity, pods with one seed and grain yield were the traits that contributed the most to genetic diversity among the soybean crosses studied. The three clustering methods used in this study were effective in representing the genetic distance in soybean. Hybridizations between lines derived from crosses CR13 and CR14 with cultivar UFUS Impact or hybridizations between lines derived from crosses CR5 and CR10 with lines derived from crosses CR21 and CR12 show promise for obtaining segregating soybean populations.